2021
DOI: 10.1139/apnm-2020-0631
|View full text |Cite
|
Sign up to set email alerts
|

Contemporaneous trajectories of physical activity and screen time in adolescents

Abstract: Adolescents often report low moderate-to-vigorous physical activity (MVPA) and high screen time. We modeled sex-specific MVPA and screen time trajectories during adolescence and identified contemporaneous patterns of evolution. Data were drawn from two longitudinal investigations. NDIT included 1294 adolescents recruited at age 12-13 who completed questionnaires every 3 months for 5 years. MATCH included 937 participants recruited at age 9-12 who completed questionnaires every 4 months for 7 years. MVPA was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(58 reference statements)
0
1
0
1
Order By: Relevance
“…Diffuser cet article sur Twitter https://doi.org/10.24095/hpcdp.42.9.03f diminue généralement de l'enfance à l'ado lescence et au début de l'âge adulte 3,4 ), une alimentation saine (comme l'atteinte de niveaux adéquats de consom mation de légumes, de fruits et de céréales complètes), les comportements de con sommation de substances (en particulier la consommation d'alcool, de tabac et de cannabis, qui peut commencer tôt et s'intensifier à l'adolescence) 5 et la sensi bilisation aux comportements agressifs (en particulier l'intimidation verbale, phy sique et cybernétique). Les IPS en milieu scolaire constituent un volet important de stratégies en santé publique plus générales qui visent à encourager les comporte ments favorables à la santé chez les enfants dès leur plus jeune âge 6 .…”
Section: Mots-clés : éColes Faisant La Promotion De La Santé Interven...unclassified
“…Diffuser cet article sur Twitter https://doi.org/10.24095/hpcdp.42.9.03f diminue généralement de l'enfance à l'ado lescence et au début de l'âge adulte 3,4 ), une alimentation saine (comme l'atteinte de niveaux adéquats de consom mation de légumes, de fruits et de céréales complètes), les comportements de con sommation de substances (en particulier la consommation d'alcool, de tabac et de cannabis, qui peut commencer tôt et s'intensifier à l'adolescence) 5 et la sensi bilisation aux comportements agressifs (en particulier l'intimidation verbale, phy sique et cybernétique). Les IPS en milieu scolaire constituent un volet important de stratégies en santé publique plus générales qui visent à encourager les comporte ments favorables à la santé chez les enfants dès leur plus jeune âge 6 .…”
Section: Mots-clés : éColes Faisant La Promotion De La Santé Interven...unclassified
“…Concerning PA, several studies have reported also different developmental trajectories for PA [43][44][45][46][47][48][49][50]. According to a recent systematic review of distinct trajectories of PA, three or four different trajectory classes were most frequently found among the reviewed studies, and several of the trajectories described a decline in PA during later childhood and adolescence [51].…”
Section: Introductionmentioning
confidence: 99%